Literature Review of Inquiry-Based Learning and Virtual Laboratories on Critical Thinking and KPS - Ahmad Fauzi; Septiana Dwi Cahyani; Gunawan Gunawan; Nina Nisrina (Indonesian Journal of Teacher Education, 2024)
Critical thinking skills and science process skills are essential competencies in 21st-century science learning. However, learning in schools is still dominated by a teacher-centered approach, thus not providing optimal opportunities for students to engage in scientific investigation activities. This study aims to analyze and synthesize research results related to the application of Inquiry-Based Learning assisted by virtual laboratories in improving students' critical thinking skills and science process skills. The method used is a literature review by analyzing 15 scientific articles from relevant national and international journals from 2015–2024 through the stages of data collection, selection, grouping, and synthesis. The results of the synthesis indicate that Inquiry-Based Learning consistently improves critical thinking skills through activities such as formulating problems, proposing hypotheses, conducting experiments, and drawing conclusions. In addition, virtual laboratories play an effective role in facilitating interactive experiments, improving conceptual understanding, and overcoming the limitations of practical facilities in schools. Overall, the integration of Inquiry-Based Learning and virtual laboratories results in more active, contextual, and student-centered learning, and is able to optimally improve higher-order thinking skills and science process skills.